Effectiveness and Predictors of Outcomes in a Psychiatric Day Treatment Program for Elementary-Age. (April 2022) - Balvardi, Sahar; Rahbari, Noriyeh; Jolicoeur-Martineau, Alexia; Rudy, Lauren; Arnovitz, Mitchell; Laplante, David P.; Brown, Maria; Habib, Paola; Zelkowitz, Phyllis; Guzder, Jaswant; Wazana, Ashley D.
Objective: In this study, we aimed to (1) assess the effectiveness of an intensive multimodal day treatment program in improving externalizing problems and function in elementary-age children and (2) examine 3 predictors of the treatment outcome (i.e., family functioning, baseline severity, and comorbid disorders). Methods: The sample included 261 children (80.9% boys) between ages of 5 and 12. A retrospective chart review, from 2013 to 2018, and a prospective chart review, from 2018 to 2019, were conducted to extract all relevant data for the present study. Parents and teachers provided reports on children's externalizing problems (i.e., aggressive behavior, attention problems, and rule-breaking behavior) and their level of function across different domains. The level of family functioning was also reported by parents, while clinicians assessed children's severity of disturbance and their diagnoses at intake. Results: Based on both parents' and teachers' reports, children showed significant improvement in their externalizing problems. Moreover, children showed functional improvement at home, at school, with peers, and in hobbies by the end of the program. Based on teacher's reports, children with lower level of severity showed less improvement in their attention problems, and those with comorbid developmental problems showed less improvement in their aggressive and rule-breaking behaviors. Family functioning did not predict any treatment outcome. Conclusion: An intensive multimodal day treatment program was effective in reducing the symptoms of externalizing problems in elementary-age children. However, children with less severe difficulties and comorbid developmental problems showed less improvement in their externalizing problems.